Discrete-time parametric amplification based on a three-terminal MOS varactor analysis and experimental results. - Ranganathan, S. (IEEE Journal of solid state circuits)
This paper discusses discrete-time parametric amplification based on large-signal operation of a three-terminal MOS varactor. The principle of operation is described in detail and analytical estimates of performance are derived. Detailed measurements are reported for a prototype implemented in standard digital CMOS technology. It is demonstrated that the technique can be used to provide micropower, low-gain, low-noise, large-signal amplification.